(untitled) (Nóema, 2014)
Carmelo Bene is not simply to be counted among the "big players" of the twentieth century, but is the author of a "genetic mutation" in theater practice. There are, in Asia, some hermits puppeteers who daily set up a show for the gods, that is for anyone, but anyone to pass, human or animal, is welcome. Acting for the desert means to embody a posture that goes beyond the duality between nature and artifice: event that bases its effectiveness in gratitude, in the surplus of life that goes from the emptiness outside to the inner one, infinitely small.